Piece of Mind: knowledge translation performances for public engagement on Parkinson’s disease and dementia - Kuhlmann, Naila; Thomas, Aliki; Incio-Serra, Natalia; Blain-Moraes, Stefanie (Frontiers in Psychology, 2024)
The subjective experience of illness is often overshadowed by the disease-and-cure focus of health research, contributing to the stigmatization of conditions such as Parkinson's disease and dementia. This is exacerbated by the fact that traditional means of knowledge dissemination are inaccessible to non-academic audiences, hampering meaningful dialogue with and research uptake by the broader community. Our arts-based knowledge translation project, Piece of Mind, brought together neuroscientists, people with Parkinson's disease or dementia, care partners and artists (musicians, dancers, circus acrobats) to co-create 2 multi-media performances based on scientific research and lived experience. We investigated whether the resulting interdisciplinary, multimedia performances could 1) challenge misperceptions around Parkinson's/dementia; and 2) render neuroscientific research accessible to a diverse audience. Prior to and immediately following virtual screenings of the feature-length Piece of Mind Parkinson's and Dementia filmed performances, audience members were invited to complete pre-post questionnaires comprised of demographic, Likert-scale and openended questions. Responses indicated that both performances elicited strong emotional engagement and improved self-reported understanding and empathy towards individuals with Parkinson's and dementia. Based on a thematic analysis on open-ended questions, we consider the barriers and facilitators to the audience's receptiveness and discuss the performances' potential as a knowledge translation tool. By presenting an emotionally engaging perspective on Parkinson's and dementia, Piece of Mind acts as an important complement to text-based knowledge dissemination in health research. social inclusion and support of people with neurodegenerative conditions (Dupuis et al., 2016;